RIVER PATTERNS AND THEIR MEANING - Twidale C.R. (My University, 2004)
Rivers are largely responsible for shaping the Earth's continental landscapes. River patterns, the spatial arrangements of channels in the landscape, are determined by slope and structure. At site and sector scale, channel morphology varies spatially and in time, but river patterns and drainage texture, or the frequency of stream lines per unit area, together determine the intricacy, or otherwise, of topography. Most river patterns evolve through natural selection. Slope induces the formation of such patterns as parallel, radial and distributary, while structure produces straight, angular, trellis and annular arrangements. Once established, patterns tend to persist. Nevertheless, at many sites the usual patterns have been disturbed and patterns that are anomalous in terms of slope and structure have been produced by diversion, tectonism, volcanism, glaciation, mass movements, and human activities; by antecedence, superimposition, inheritance or underprinting; by the persistence of deeply eroding rivers which encounter alien structures; and by climatic change. River patterns provide clues to underlying structure and to the chronology of events. They have also proved significant in the search for minerals.
Keywords: River pattern; Natural selection; Adjusted streams; Anomalous streams; Climatic change; Inversion